2017
DOI: 10.1016/j.arr.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation – inflammaging – in the ageing cochlea: A novel target for future presbycusis therapy

Abstract: Chronic, low-grade inflammation, or inflammaging, is a crucial contributor to various age-related pathologies and natural processes in aging tissue, including the nervous system. Over the past two decades, much effort has been done to understand the mechanisms of inflammaging in disease models such as type II diabetes, cardiovascular disease, Alzheimer’s disease, Parkinson’s disease, and others. However, despite being the most prevalent neurodegenerative disorder, the number one communication disorder, and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 74 publications
3
108
0
4
Order By: Relevance
“…Aging is characterized by increased oxidative stress and inflammation, and has been reported to have a relationship with ARHL and chronic inflammatory diseases, such as diabetes and cardiovascular disease (Watson et al, ). Additionally, previous studies have demonstrated that increased ROS production and pro‐inflammatory cytokines, such as TNF‐α, IL‐1β, and IL‐6, play critical roles in cochlear tissue damage, in noise‐ or cisplatin‐induced hearing loss (Fujioka et al, ; So et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aging is characterized by increased oxidative stress and inflammation, and has been reported to have a relationship with ARHL and chronic inflammatory diseases, such as diabetes and cardiovascular disease (Watson et al, ). Additionally, previous studies have demonstrated that increased ROS production and pro‐inflammatory cytokines, such as TNF‐α, IL‐1β, and IL‐6, play critical roles in cochlear tissue damage, in noise‐ or cisplatin‐induced hearing loss (Fujioka et al, ; So et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…NF‐κB transcription factor is considered as the master regulator of the inflammatory response, which is associated with the development and pathogenesis of various age‐related diseases, including ARHL (Kubben & Misteli, ; Watson et al, ). According to a recent report, daily fasting (a type of dietary restriction) protects the rat heart against age‐induced inflammation and fibrosis, by suppressing NF‐κB activation and oxidative damage, indicating the preventive effect of NF‐κB inhibition, on age‐related diseases (Castello et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also dampens the effect of vaccination ( 6 8 ) and can lead to higher cancer susceptibility ( 9 – 12 ). These changes may further result in an imbalanced immune response that can develop into non-specific inflammation, provoking neurodegenerative and cardiovascular disorders, and to the loss of tolerance, leading to autoimmunity ( 3 , 13 15 ). For the latter, a reduction of regulatory T cell (Treg) diversity ( 16 , 17 ) could be a one of the causative factors.…”
Section: Introductionmentioning
confidence: 99%
“…Our study supports both these mechanisms, given that inflammation and several CVD risk factors such as smoking, physical inactivity and obesity were predictive of an increased risk of hearing impairment. Inflammageing-related diseases such as obesity, hypertension and type 2 diabetes have been linked to poorer hearing in previous studies 43 . Moreover, our results and a large body of studies, including animal models, make a direct inflammatory role plausible in the aetiology of age-related hearing loss.…”
Section: And Thementioning
confidence: 92%